A battery
Patent Information
- Application Number
- CN202611274176.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-16
AI Technical Summary
[0004]为了改善因在正极片的表面设置凹槽而导致的正极片凹槽边缘与隔膜的粘接性能变差和隔膜被刺穿的风险增加的问题,本发明提供了一种电池
本发明的电池,其通过采用基材层的穿刺强度在200gf以上的隔膜、控制凹槽边缘第一区域中第一正极活性颗粒的长径小于或等于30μm以及限定负极活性层中硅元素的含量,三者协同以显著改善电池的自放电现象并提高电池的循环性能,具体而言:通过控制负极活性层中硅元素的重量占比在上述范围,可有效管控硅颗粒膨胀对隔膜的整体挤压程度,同时上述隔膜能够束缚硅基材料的膨胀,进一步降低膨胀应力;在此基础上,控制凹槽边缘第一正极活性颗粒的长径和隔膜的基材层的穿刺强度在上述范围,一方面,控制第一正极活性颗粒的长径在合适的范围能够降低凹槽边缘与隔膜的界面的空隙,提高正极片凹槽边缘与隔膜的界面性能;另一方面,长径适中的第一正极活性颗粒不会形成刺穿性应力集中,且基材层穿刺强度较高的隔膜,能够提高隔膜的结构稳定性,为第一正极活性颗粒提供稳定的抵接界面,有利于维持凹槽边缘与隔膜之间的良好粘接性能,进一步降低电池自放电水平的同时提高电池的循环性能。
Smart Images

Figure CN122930890A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and more specifically to a battery. Background Technology
[0002] With the continuous increase in energy density requirements for lithium-ion batteries in the fields of new energy vehicles, consumer electronics, and energy storage, the current main development trend is to continuously increase the proportion of silicon materials in the negative electrode active material. However, in battery design, to ensure the balance of positive and negative electrode capacity, and while maintaining the positive electrode compaction density within the optimal range, the industry generally adopts the method of increasing the thickness of the positive electrode active coating to improve the total loading of the positive electrode. However, increasing the thickness of the positive electrode coating will significantly lengthen the path for the electrolyte to penetrate into the electrode, resulting in a significant increase in wetting resistance, which in turn affects the cycle performance of the battery. Summary of the Invention
[0003] To improve the wettability of the electrolyte on the positive electrode, the inventors of this invention employed a method of creating grooves on the surface of the positive electrode (e.g., through laser scribing) to increase the contact area between the electrolyte and the electrode and shorten the wetting path. However, research has shown that creating grooves on the surface of the positive electrode through laser scribing leads to a decrease in the adhesion between the groove edges and the separator. Furthermore, the laser scribing process can easily cause sharp positive electrode active particles to detach from the active layer, pierce the separator, and trigger severe self-discharge.
[0004] To address the problems of reduced adhesion between the positive electrode groove edge and the separator, and increased risk of separator puncture, caused by grooves on the surface of the positive electrode, this invention provides a battery. The battery of this invention improves the adhesion between the positive electrode groove edge and the separator, while also reducing damage to the separator from sharp active particles generated on the positive electrode surface due to the grooves, thereby significantly reducing the battery's self-discharge level and improving its cycle performance.
[0005] To achieve the above objectives, the present invention provides a battery including an electrode assembly. The electrode assembly includes a positive electrode sheet, a separator, and a negative electrode sheet stacked together. The positive electrode sheet includes a positive current collector and a positive active layer located on at least one side surface of the positive current collector. The positive active layer includes positive active particles. The surface of the positive active layer away from the positive current collector is a first surface. The first surface includes at least one groove region. The groove region is provided with a plurality of grooves at intervals. The average depth of the grooves is H1. In at least one of the grooves, the edge of the groove includes a first region at a distance of 0-0.5H1 from the first surface. The first region includes a first positive active particle. The major axis of the first positive active particle is less than or equal to 30 μm. The puncture strength of the substrate layer of the diaphragm is greater than or equal to 200 gf, and the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer located on at least one side surface of the negative electrode current collector. Based on the total weight of the negative electrode active layer, the weight ratio of silicon element is less than or equal to 50%.
[0006] By employing the above technical solution, the present invention has at least the following advantages compared with the prior art: The battery of the present invention significantly improves the self-discharge phenomenon and enhances the cycle performance of the battery by employing a separator with a substrate layer puncture strength of 200 gf or more, controlling the major diameter of the first positive electrode active particles in the first region of the groove edge to be less than or equal to 30 μm, and limiting the silicon content in the negative electrode active layer. Specifically, by controlling the weight ratio of silicon in the negative electrode active layer within the above-mentioned range, the overall compression of the separator by silicon particle expansion can be effectively controlled. At the same time, the separator can restrain the expansion of the silicon-based material, further reducing expansion stress. On this basis, the major diameter of the first positive electrode active particles in the groove edge is controlled to be less than or equal to 30 μm. When the long diameter of the particles and the puncture strength of the substrate layer of the separator are within the aforementioned range, on the one hand, controlling the long diameter of the first positive electrode active particles within a suitable range can reduce the voids at the interface between the groove edge and the separator, thereby improving the interface performance between the groove edge of the positive electrode sheet and the separator; on the other hand, the first positive electrode active particles with a moderate long diameter will not form puncture stress concentration, and the separator with a high puncture strength of the substrate layer can improve the structural stability of the separator, provide a stable contact interface for the first positive electrode active particles, and help maintain good adhesion between the groove edge and the separator, thereby further reducing the battery's self-discharge level while improving the battery's cycle performance.
[0007] Other features and advantages of the present invention will be described in detail in the following detailed description section.
[0008] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. Attached Figure Description
[0009] Figure 1 The diagram shown is a cross-sectional schematic of the positive electrode of the battery of the present invention.
[0010] Figure 2 The diagram shown is a schematic representation of the first region of the groove edge of the positive electrode plate of the battery of the present invention.
[0011] Figure 3 The image shown is one of the schematic diagrams of the groove on the first surface of the battery of the present invention.
[0012] Figure 4 The diagram shown is a cross-sectional structural schematic of the electrode assembly of the battery of the present invention.
[0013] Figure 5 The image shown is a cross-sectional SEM image of the silicon-carbon particles of the present invention.
[0014] Figure 6 The image shown is a second schematic diagram of the groove on the first surface of the battery of the present invention.
[0015] Figure 7 The diagram shows the first, second, and third regions of the positive electrode sheet of the present invention in a flat state. Detailed Implementation
[0016] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the invention. Unless otherwise specified herein, data ranges include endpoints.
[0017] It should be noted that the numerical designations such as "first" and "second" in this invention are only used to distinguish different substances or methods of use, and do not represent a difference in order.
[0018] This invention provides a battery including an electrode assembly. The electrode assembly includes a positive electrode sheet, a separator, and a negative electrode sheet stacked together. The positive electrode sheet includes a positive current collector and a positive active layer located on at least one surface of the positive current collector. The positive active layer includes positive active particles. The surface of the positive active layer away from the positive current collector is a first surface. The first surface includes at least one groove region. The groove region is provided with a plurality of grooves at intervals. The average depth of the grooves is H1. In at least one of the grooves, the edge of the groove includes a first region at a distance of 0-0.5H1 from the first surface. The first region includes a first positive active particle. The major axis of the first positive active particle is less than or equal to 30 μm (e.g., 10 μm, 13 μm, 15 μm, 18 μm, 20 μm, 23 μm, 25 μm, 28 μm, 30 μm, or within any two of the above values). The puncture strength of the substrate layer of the diaphragm is greater than or equal to 200gf (e.g., 200gf, 230gf, 250gf, 280gf, 300gf, 330gf, 350gf, 380gf, 400gf, 430gf, 450gf, 480gf, 500gf, 530gf, 550gf, 580gf, 600gf or within any two of the above values). The negative electrode sheet includes a negative electrode current collector and a negative electrode active layer located on at least one side surface of the negative electrode current collector. Based on the total weight of the negative electrode active layer, the weight percentage of silicon is less than or equal to 50% (e.g., 1%, 2%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or within any two of the above values).
[0019] like Figure 1 and Figure 3 As shown, the positive electrode sheet 1 includes a positive current collector 11 and a positive active layer 12 located on at least one side surface of the positive current collector 11. The surface of the positive active layer 12 away from the positive current collector 11 is a first surface 121, which includes at least one groove region 1211, and the groove region 1211 is provided with a plurality of grooves 12111 spaced apart. It can be understood that when the positive active layer is located on one side surface of the positive current collector, the surface of the positive active layer away from the positive current collector is the first surface, and the first surface is provided with at least one groove region; when the positive active layer is located on both sides of the positive current collector, the surfaces of both positive active layers away from the positive current collector are both first surfaces, and at least one groove region can be provided on the first surface of one side of the positive active layer, or at least one groove region can be provided on the first surfaces of both sides of the positive active layer. Figure 1 In the diagram, X represents the width of the positive electrode, Y represents the thickness of the positive electrode, and Z represents the length of the positive electrode.
[0020] like Figure 2 As shown, the region 0-0.5H1 from the first surface is the first region 121111, which includes the first positive electrode active particle 1221. In this invention, the major diameter of the first positive electrode active particle can be obtained by taking a cross-sectional image of the positive electrode active layer using a scanning electron microscope (SEM). In the image, a square or rectangle with the smallest area tangent to a complete first positive electrode active particle is drawn; that is, a square or rectangle with the edge of a complete first positive electrode active particle tangent to all four sides of the square or rectangle is drawn. The side length of the square or the length of the long side of the rectangle is the major diameter of the first positive electrode active particle. It is understood that the major diameter of the first positive electrode active particle refers to the major diameter of a single first positive electrode active particle.
[0021] In the battery of the present invention, by controlling the major and minor diameters of the first positive electrode active particles located in the first region within the aforementioned range, the risk of puncture-induced stress concentration caused by the expansion stress of the first positive electrode active particles can be reduced, thereby reducing the risk of the separator being damaged or even punctured by the first positive electrode active particles. The battery of the present invention also controls the weight percentage of silicon in the negative electrode active layer to be below 50% to manage the overall compression of the separator by silicon particle expansion. Simultaneously, by controlling the puncture strength of the separator's substrate layer within the aforementioned range, on the one hand, the separator can restrain the expansion of the silicon-based material, further reducing expansion stress; on the other hand, a separator with higher puncture strength in the substrate layer can improve the structural stability of the separator, providing a stable contact interface for the first positive electrode active particles. Combined with the aforementioned first positive electrode active particles of suitable particle size, this helps maintain good adhesion between the first positive electrode active particles and the separator, thereby reducing the battery's self-discharge level and improving its cycle performance.
[0022] When the particle size of the first positive electrode active particle is too large, for example, above 30 μm, this particle not only becomes a stress concentration point, posing a risk of puncturing the separator, but also results in excessively large interfacial gaps between the groove edge and the separator, deteriorating the interfacial performance between the positive electrode and the separator and reducing interfacial adhesion. When the particle size of the first positive electrode active particle is too small, for example, less than 10 μm, there are no anchoring points between the groove edge and the separator, causing the separator to sink into the groove. During later cycles, the separator is repeatedly stretched, posing a risk of rupture, which can lead to micro-short circuits between the positive and negative electrodes, thus hindering the improvement of battery self-discharge. When the puncture strength of the separator substrate layer is higher than 600 gf, although it can restrain the expansion of silicon-carbon particles, it reduces the wetting performance of the electrolyte on the separator, affecting the battery's cycle performance. When the puncture strength of the separator substrate layer is lower than 200 gf, the structural stability of the separator is poor, and the first positive electrode active particle is prone to puncturing the separator, leading to a deterioration in the battery's self-discharge level.
[0023] In this invention, the puncture strength of the substrate layer of the separator can be obtained by conventional testing methods in the art: for example, the separator is removed from the battery cell, and the separator is selected at the head, tail, or superanode region of the battery cell where it is not bonded to the electrode. The separator is cleaned with anhydrous ethanol to remove electrolyte and residual lithium salt, and then placed in a vacuum oven at 40°C to dry and remove the solvent, thus obtaining the separator. The coating on the surface of the substrate layer is removed. When the residual coating on the surface of the substrate layer is less than 5%, it is considered as obtaining a test sample of the substrate layer. Alternatively, the original substrate without coating can be used. The substrate layer is used as the test sample. A 50mm × 50mm sample is arbitrarily cut from the test sample. The sample is laid flat in the clamp of the universal tensile testing machine and clamped. The puncture strength test is selected, and puncture is performed at a rate of (100±10) mm / min. The puncture strength test result is read from the test report. This is repeated three times, and the average value is taken as the puncture strength of the substrate layer. The puncture strength of the diaphragm substrate layer is tested when the diaphragm is flattened; "flattened" means the diaphragm is neither bent nor stretched. In this invention, the puncture strength of the diaphragm substrate layer can be controlled by changing at least one of the following: the molecular weight of the diaphragm substrate layer and the preparation process.
[0024] In this invention, the weight percentage of silicon element is determined using conventional testing methods in the art, based on the total weight of the negative electrode active layer. For example, after disassembling a lithium-ion battery, the negative electrode sheet is removed, soaked and rinsed with dimethyl carbonate, and then dried. The dried negative electrode sheet is then subjected to high-temperature treatment at 400°C for 2 hours (e.g., in a tube furnace under nitrogen or argon atmosphere). The negative electrode active material layer can then be peeled off from the current collector, and the negative electrode active material can be collected. In the silicon content test, a thermogravimetric analyzer (e.g., a TGA 550 thermogravimetric analyzer) is used. The sample amount is 5mg-15mg. Under an air or oxygen atmosphere, the temperature is increased from room temperature to 900°C at a rate of 10°C / min, and held at 900°C for 40 minutes. This allows the non-silicon components in the negative electrode active layer to volatilize while the silicon is fully oxidized to silicon dioxide. The weight percentage at the end of the entire test process is the ash content of the negative electrode active layer; dividing this ash content by the molar mass of silicon dioxide and then multiplying it by the molar mass of silicon gives the percentage content of silicon in the negative electrode active layer.
[0025] In some embodiments, the puncture strength of the substrate layer of the diaphragm is 200gf-600gf.
[0026] In some embodiments, the first region of all the grooves includes a first positive electrode active particle with a major diameter less than or equal to 30 μm.
[0027] In some embodiments, the major diameter of the first positive electrode active particle is 10 μm-30 μm.
[0028] In some embodiments, the first region of at least one groove includes a first positive electrode active particle with a major diameter of 10 μm-30 μm.
[0029] In some embodiments, the first region of all the grooves includes a first positive electrode active particle with a major diameter of 10 μm-30 μm.
[0030] In some embodiments, the battery satisfies the following relationship: 0.2≤H1 / H2≤0.5 (for example, 0.2, 0.23, 0.25, 0.28, 0.3, 0.33, 0.35, 0.38, 0.4, 0.43, 0.45, 0.48, 0.5 or within any two of the above values), where H2 is the thickness of the positive electrode active layer on one side.
[0031] It is understandable that when the positive electrode active layer is located on both sides of the positive electrode current collector, and multiple grooves are provided at intervals on the first surface of the positive electrode active layer on only one side, the thickness H2 of the positive electrode active layer on one side refers to the thickness of the positive electrode active layer on the side with the grooves. When multiple grooves are provided at intervals on the first surface of both positive electrode active layers, the grooves and the positive electrode active layer on the side with the grooves satisfy the relationship: 0.2≤H1 / H2≤0.5. For example, the positive electrode active layer located on one side of the positive electrode current collector is the first active layer, and the positive electrode active layer located on the other side of the positive electrode current collector is the second active layer. The first surface of the first active layer is provided with multiple first grooves at intervals, and the first surface of the second active layer is provided with multiple second grooves at intervals. Then, the ratio of the average depth of the first groove to the thickness of the first active layer is 0.2-0.5, and / or the ratio of the average depth of the second groove to the thickness of the second active layer is 0.2-0.5.
[0032] In some embodiments, the average depth H1 of the groove is greater than or equal to 5 μm (e.g., 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm or within any two of the above values).
[0033] In this invention, the average depth of the groove can be obtained by testing as follows: Ten test sites (with equal spacing) are taken at equal intervals along the groove extension direction. The depth of each of the ten test sites is measured using a 3D profilometer, and the average depth of the ten test sites is taken as the average depth of the groove. The depth of the test site refers to the perpendicular distance from the test site to the first surface in the thickness direction of the positive electrode sheet.
[0034] In some embodiments, the width of the groove is 20μm-200μm (e.g., 20μm, 40μm, 60μm, 80μm, 100μm, 120μm, 140μm, 160μm, 180μm, 200μm or within any two of the above values).
[0035] In this invention, the width of the groove is the average width of the groove, which can be obtained by measuring the average width of individual grooves in a system. The width of a single groove refers to the average distance between the two long sides of the single groove in the orthographic projection onto the first surface. For example, 10 points are randomly selected on any one of the long sides, the width corresponding to each point is measured, and the average value is taken as the average distance between the two long sides. The width of a single groove can be obtained by testing with a 3D profilometer or SEM image.
[0036] In some embodiments, the spacing between any two adjacent grooves is 0.1mm-5mm (e.g., 0.1mm, 0.5mm, 1mm, 1.5mm, 2mm, 2.5mm, 3mm, 3.5mm, 4mm, 4.5mm, 5mm, or within any two of the above values). In this invention, the spacing between any two adjacent grooves refers to the distance between the edge lines of two adjacent grooves.
[0037] Controlling one or more of the average depth of the groove, the width of the groove, and the spacing between any two adjacent grooves within the above range can not only increase the contact area between the electrolyte and the positive electrode and shorten the wetting path, but also improve the adhesion performance between the groove edge and the separator, further reducing the self-discharge level of the battery and improving the cycle performance of the battery.
[0038] In this invention, the shape of the groove projected along the width direction of the positive electrode sheet includes at least one of a square, a rectangle, a triangle, and a trapezoid.
[0039] In some embodiments, in the extending direction of the groove, the difference in distance from the bottom of the groove to the first surface at any two locations within a single groove is 0-3 μm (e.g., 0, 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, or within any two of the above values). Controlling the difference in distance from the bottom of the groove to the first surface at any two locations within the above range in the extending direction of the groove facilitates a uniform distribution of the first positive electrode active particles along the extending direction of the groove at the edge of the groove. This further improves the adhesion between the groove edge and the separator, thereby further reducing the battery's self-discharge level and improving its cycle performance.
[0040] In this invention, "the difference in depth between any two locations of the groove in the extending direction of the groove" refers to, for example, Figure 3 As shown, in the extension direction A of the groove, the difference in depth between any two different positions within the same groove, for example, in the extension direction A of the groove, if two different positions B1 and B2 are arbitrarily selected within the same groove, the difference in depth between positions B1 and B2 is the difference in depth between any two positions within the groove in the extension direction of the groove. It can be understood that, for example, the depth at position B1 refers to the perpendicular distance from position B1 to the first surface in the thickness direction of the positive electrode sheet.
[0041] It is understood that when the first surface has one groove, the groove satisfies the following condition: in the extending direction of the groove, the depth difference between any two positions of the groove is 0-3 μm. When the first surface has multiple grooves, all the grooves satisfy the following condition: in the extending direction of the groove, the depth difference between any two positions of the groove is 0-3 μm.
[0042] In this invention, the depth difference between any two positions of a single groove in the extension direction of the groove can be obtained by the following method: within a length of 3cm in the extension direction of the groove, arbitrarily select two different positions, use a 3D profilometer to measure the depth at the two different positions respectively, and then calculate the depth difference between the two different positions. Repeat the above operation 3 times and take the average value as the final test result.
[0043] In this invention, "multiple grooves" refers to one or more grooves.
[0044] In some embodiments, the extension direction of the groove, within a single groove, has a maximum groove depth difference of 5 μm to 15 μm (e.g., 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, or within any two of the above values). Controlling the difference between the maximum and minimum groove depths within the above range is beneficial for ensuring better uniformity of the major axis of the first positive electrode active particles formed in a single groove, avoiding discontinuous adhesion between the groove edge and the separator, thereby improving the cycle performance of the battery.
[0045] In this invention, the difference between the maximum and minimum groove depth in a single groove can be obtained by testing as follows: within a length of 3 cm in the extension direction of the groove, the depth of the groove at 50 different locations is measured using a 3D profilometer, and then the difference between the maximum and minimum groove depth is calculated. The above operation is repeated 3 times, and the average value is taken as the final test result.
[0046] To further improve the energy density of lithium-ion batteries, wound cell structures are often used. However, due to the special characteristics of wound cell structures, the arc regions of wound cells not only present difficulties in electrolyte wetting but also are prone to lithium plating. Therefore, in wound cell structures, groove regions are further provided in at least one first bending segment, thereby improving electrolyte wetting while further reducing the risk of lithium plating. In some embodiments, the electrode assembly includes a flat region and arc regions located at both ends of the flat region; the positive electrode includes a plurality of first bending segments located in the arc regions and arranged sequentially from the inside to the outside, and at least one of the first bending segments is provided with the groove region.
[0047] In this invention, such as Figure 4 As shown, the electrode assembly 10 includes a flat region 101 and arcuate regions 102 located at both ends of the flat region 101; the positive electrode sheet 1 includes a plurality of first bent segments 111 located in the arcuate regions 102 and arranged sequentially from the inside to the outside. Here, "from the inside to the outside" means that they are distributed sequentially from the winding center of the electrode assembly along the horizontal direction of the cross-section of the electrode assembly, moving away from the winding center of the electrode assembly. Figure 4 As shown, the direction of N is from the inside out.
[0048] In some embodiments, the positive electrode active layer has two opposing ends along the first direction M, and the groove connects the two ends (e.g., Figure 3 (As shown).
[0049] In some embodiments, the positive electrode active layer has two opposing ends along the first direction M, and the groove is spaced d from both ends (e.g., ...). Figure 6 (As shown).
[0050] The first direction M refers to the width direction X of the positive electrode plate.
[0051] In some embodiments, along the winding direction of the positive electrode sheet, the difference between the widths of any two different groove regions is less than or equal to 2 mm. Controlling the difference between the widths of any two different groove regions within this range ensures that the projection of the groove side of each arc region onto the thickness direction of the winding core is approximately a straight line during core formation. This effectively avoids uneven shear force distribution at the groove edges during cell formation, which could damage the separator and further reduce the risk of short circuits in the cell.
[0052] In some embodiments, the width D of the groove area is 6mm-12mm (e.g., 6mm, 7mm, 8mm, 9mm, 10mm, 11mm, 12mm or a range between any two of the above values).
[0053] In this invention, such as Figure 3 As shown, the width D of the groove region 1211 refers to the groove with the furthest distance between its two sides in a single groove region 1211 along the length direction Z of the positive electrode sheet (i.e., the winding direction of the positive electrode sheet). Figure 3 The distance between the edge lines (e.g., 12112 and 12113) of the two grooves enclosed by solid circles in the groove region represents the distance between the edge lines of the two grooves furthest apart in the groove region. For example, 10 points are randomly selected on the edge line (e.g., 12112) of one of the grooves furthest apart in a single groove region, and the shortest distance between each point and the edge line of the other groove (e.g., 12113) is tested. The average of these distances is taken as the width of the groove region. It can be understood that when the first surface has multiple groove regions, the width of the groove region is the average width of the multiple groove regions.
[0054] In other embodiments, the electrode assembly includes a flat region and arcuate regions located at both ends of the flat region (see reference). Figure 4The positive electrode includes a plurality of first bending segments arranged sequentially from the inside to the outside in the arc region. Each of the plurality of first bending segments is provided with a groove region. Along the radial direction of the electrode assembly from the inside to the outside, the first N first bending segments constitute a first region, the (N+1)th to (N+M)th first bending segments constitute a second region, and the (N+M+1)th to (N+M+Q)th first bending segments constitute a third region. The width of the grooved area in the first region is W1, the width of the grooved area in the second region is W2, and the width of the grooved area in the third region is W3, wherein W1 < W2 < W3; 4 ≤ N ≤ 8 (e.g., 4, 5, 6, 7, 8), 3 ≤ M ≤ 10 (e.g., 3, 4, 5, 6, 7, 8, 9, 10), and 5 ≤ Q ≤ 35 (e.g., 5, 8, 10, 13, 15, 18, 20, 23, 25, 28, 30, 33, 35, or an integer between any two of the above values). This configuration can improve the wettability of the electrolyte, reduce the risk of severe lithium plating, and simultaneously reduce the loss of positive electrode active particles in the arc-shaped region, enabling the battery to possess both a lower risk of severe lithium plating and a higher energy density.
[0055] like Figure 7 As shown, taking one of the arc regions as an example, for instance, this arc region includes 12 first bending segments 111, N is 4, M is 3, and Q is 5. Then, the first 4 (N) first bending segments are the first region 01, the 5th to 7th first bending segments are the second region 02, and the 8th to 12th first bending segments are the third region 03. The width of the groove region in the third region 03 is denoted as W3, the width of the groove region in the second region 02 is denoted as W2, and the width of the groove region in the first region 01 is denoted as W1, where W1 < W2 < W3.
[0056] In some embodiments, W1 is 2mm-5mm (e.g., 2mm, 2.3mm, 2.5mm, 2.8mm, 3mm, 3.3mm, 3.5mm, 3.8mm, 4mm, 4.3mm, 4.5mm, 4.8mm, 5mm or any two of the above values), W2 is 4mm-8mm (e.g., 4mm, 4.5mm, 5mm, 5.5mm, 6mm, 6.5mm, 7mm, 7.5mm, 8mm or any two of the above values), and W3 is 6mm-12mm (e.g., 6mm, 6.5mm, 7mm, 7.5mm, 8mm, 8.5mm, 9mm, 9.5mm, 10mm, 10.5mm, 11mm, 11.5mm, 12mm or any two of the above values).
[0057] In some embodiments, W1 is 2mm-5mm, W2 is 4mm-8mm, W3 is 6mm-12mm, and W1 < W2 < W3.
[0058] In some embodiments, the positive electrode active particles include a first particle and a second particle, wherein the median particle size Dv50 of the first particle is 12μm-20μm (e.g., 12μm, 14μm, 16μm, 18μm, 20μm or within any two of the above values), and the median particle size Dv50 of the second particle is 2μm-5μm (e.g., 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm or within any two of the above values), and the weight ratio of the first particle to the second particle is (6-9):(1-4).
[0059] By controlling the median particle size of the first particle to be within the aforementioned range, the median particle size of the second particle to be within the aforementioned range, or the weight ratio of the first particle to the second particle, it is possible to control the major diameter of the first positive electrode active particle in the first region at the edge of the groove to be within the range of 10μm-30μm after the groove is laser-formed on the surface of the positive electrode sheet. This can improve the adhesion performance between the groove edge and the separator, while the first positive electrode active particle will not cause damage or puncture to the separator, thereby further reducing the self-discharge level of the battery and improving the cycle performance of the battery.
[0060] In this invention, by controlling one or more of the median particle size of the first particle, the median particle size of the second particle, and the weight ratio of the first particle to the second particle, and based on different combinations of the first particle and the second particle, or by controlling the laser scribing process conditions, it can be ensured that the major diameter of the first positive electrode active particle in the first region at the edge of the groove is controlled within the range of 10μm-30μm.
[0061] In this invention, the weight ratio of the first particle to the second particle being (6-9):(1-4) means that the weight percentage of the first particle in the positive electrode active particle can be in the range of 60%-90% (e.g., 60%, 65%, 70%, 75%, 80%, 85%, 90% or within any two of the above values), and the weight percentage of the second particle in the positive electrode active particle can be in the range of 10%-40% (e.g., 10%, 15%, 20%, 25%, 30%, 35%, 40% or within any two of the above values). However, it is required that the sum of the weight percentage of the first particle in the positive electrode active particle and the weight percentage of the second particle in the positive electrode active particle is 100%.
[0062] In this invention, the median particle size Dv50 of the first particle refers to the particle size corresponding to 50% of the cumulative particle size distribution in the volumetric particle size distribution of the first particle. The median particle size Dv50 of the second particle refers to the particle size corresponding to 50% of the cumulative particle size distribution in the volumetric particle size distribution of the second particle. Both the volumetric particle size distributions of the first and second particles can be obtained by testing with a laser particle size analyzer.
[0063] In some embodiments, the positive electrode active particles comprise at least one of lithium cobalt oxide and lithium iron phosphate.
[0064] In a preferred embodiment, the positive electrode active particles comprise lithium cobalt oxide.
[0065] In some embodiments, the positive electrode active layer further includes a positive electrode conductive agent and a positive electrode binder.
[0066] In some embodiments, the positive electrode conductive agent includes one or more of conductive carbon black, carbon nanotubes, conductive graphite, and graphene.
[0067] In some embodiments, the positive electrode binder includes one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-acrylonitrile copolymer, polyurethane, polyimide, polyacrylic acid, polytetrafluoroethylene, perfluorosulfonic acid ionomer, and polyacrylonitrile.
[0068] In some embodiments, based on the total weight of the positive electrode active layer, the weight percentage of the lithium cobalt oxide material is 90%-98.5% (e.g., 90%, 90.5%, 91%, 91.5%, 92%, 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 98.5%, or within any two of the above values), the weight percentage of the positive electrode conductive agent is 0.5%-1.5% (e.g., 0.5%, 0.8%, 1%, 1.3%, 1.5%, or within any two of the above values), and the weight percentage of the positive electrode binder is 0.5%-1.5% (e.g., 0.5%, 0.8%, 1%, 1.3%, 1.5%, or within any two of the above values).
[0069] In some embodiments, the weight percentage of silicon is 2%-50% based on the total weight of the negative electrode active layer.
[0070] In some embodiments, the negative electrode active layer comprises silicon-carbon particles, the cross-sectional profile of which has a first interior angle, denoted as B°, where B > 180° (e.g., 181°, 190°, 200°, 210°, 220°, 230°, 240°, 250°, 260°, 270°, 280°, 290°, 300°, or within any two of the above values). Selecting silicon-carbon particles with the aforementioned first interior angle and controlling it within the above range ensures that when the silicon-carbon particles break due to expansion and compression, they will preferentially break at the first interior angle, avoiding sharp edges after breakage. This reduces the risk of the separator being punctured, thereby further reducing the battery's self-discharge level.
[0071] In this invention, the first interior angle refers to the angle formed by drawing two straight lines tangent to the cross-sectional profile of a silicon-carbon particle in a scanning electron microscope (SEM) image of the particle, starting from a point on the cross-sectional profile closer to the center of the particle. The included angle between these two tangent lines is the first interior angle. Figure 5 The angle ∠BAC is shown. The angle of the first interior angle can be obtained by conventional testing methods in the art, such as by scanning electron microscopy (SEM), specifically as follows: Discharge the battery to 0% SOC, disassemble and remove the negative electrode, or directly remove the negative electrode, polish its cross-section with an argon ion mill, and then image the obtained cross-section using backscatter imaging on a scanning electron microscope (SEM) device. In the cross-sectional contour of the silicon-carbon particles, use image analysis software (e.g., ImageJ, NanoMeasurer, Matlab, ParticleMetric, etc.) to obtain the image. Figure 5 As shown, in the cross-sectional SEM image of a randomly selected single silicon carbide particle 21, taking the point on the cross-sectional profile of the silicon carbide particle 21 that is closer to the center of the cross-section of the silicon carbide particle as the starting point (for example, A), two straight lines (AB and AC) tangent to the cross-sectional profile of the particle are drawn respectively. The interior angle (∠BAC) formed by the two tangent lines inside the silicon carbide particle with an angle greater than 180° is the first interior angle. The angle of this interior angle is the first interior angle. A total of 10 different silicon carbide particles were measured, and the average value was taken as the angle of the first interior angle.
[0072] In some embodiments, the negative electrode active layer includes a first active layer and a second active layer, the first active layer being located between the negative electrode current collector and the second active layer, the first active layer comprising graphite, and the second active layer comprising first silicon-carbon particles.
[0073] In some embodiments, the first active layer further includes second silicon-carbon particles, wherein the weight percentage of silicon in the second active layer is greater than that in the first active layer. Based on this difference in silicon content, the second active layer, with its higher silicon content, can provide sufficient lithium storage active sites, thereby effectively suppressing or preventing lithium plating. Simultaneously, the first active layer, with its lower silicon content or the use of pure graphite as the active material, is positioned close to the current collector, providing structural support and mitigating volume expansion. Therefore, this layered structure design not only reduces the overall expansion rate of the negative electrode but also further suppresses the increase in the K value, reducing the risk of short circuits caused by the negative electrode expanding and compressing the separator, thereby further reducing the battery's self-discharge level.
[0074] In some embodiments, the weight percentage of the second silicon-carbon particles in the first active layer is 0-15% (e.g., 0, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, or within any two of the above values), and the weight percentage of the first silicon-carbon particles in the second active layer is 10%-90% (e.g., 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, or within any two of the above values). It is understood that when the weight percentage of the second silicon-carbon particles in the first active layer is 0, it indicates that the active material in the first active layer is pure graphite.
[0075] In some embodiments, the outlines of both the first silicon carbide particle and the second silicon carbide particle have a first interior angle.
[0076] In some embodiments, the negative electrode active layer includes a negative electrode conductive agent and a negative electrode binder.
[0077] In some embodiments, the negative electrode conductive agent includes one or more of conductive carbon black, acetylene black, Ketjen black, conductive graphite, single-walled carbon nanotubes, multi-walled carbon nanotubes, conductive carbon fibers, carbon nanotubes, metal powder, graphene, and carbon fibers.
[0078] In some embodiments, the negative electrode binder includes one or more of styrene-butadiene rubber (SBR), fluoropolymers, lithium polyacrylate (PAALi), acrylonitrile polymers, polyacrylic acid (PAA), polyurethane, sodium polymethylcellulose (CMC-NA), and lithium polymethylcellulose (CMC-Li).
[0079] In some embodiments, the separator includes a carrier layer and a polymer layer located on at least one side of the carrier layer. The polymer layer includes a plurality of protrusions formed of a first polymer on its surface away from the carrier layer. Adjacent protrusions can form a plurality of cavities with the electrode. These cavities can, on the one hand, improve the insufficient wettability caused by the high puncture strength of the separator's substrate layer, increase the liquid retention and ionic conductivity at the separator-electrode interface, thereby improving the battery's long-cycle performance. On the other hand, the cavities can also accommodate or enclose particles that detach from the groove edges, reducing or even preventing the detached particles from moving freely and puncturing the separator, thereby further reducing the battery's self-discharge level.
[0080] In some embodiments, the average height of the protrusion is 0.5μm-15μm (e.g., 0.5μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, or within any two of the above values). Controlling the average height of the protrusion within the above range can, on the one hand, avoid the problem of particles detaching from the edge of the groove piercing the separator and the increase of the K value due to the protrusion height being too small; on the other hand, it can ensure good adhesion between the separator and the electrode interface, thereby further improving the long-cycle performance of the battery.
[0081] In this invention, the average height of the protrusion can be obtained by the following method: Using a scanning electron microscope to obtain an SEM image of the membrane cross-section, arbitrarily select an area of 100μm × 100μm on the polymer layer surface, and measure the height of 50 protrusions within this area. The average height of these 50 protrusions is the average height. Repeat this operation 5 times, and take the average of the 5 test results as the height of the protrusion protruding from the polymer layer surface. If the number of protrusions is less than 50, change the location and continue measuring until 50 are found. The height of the protrusion is the dimension of the portion of the protrusion protruding from the polymer layer surface.
[0082] In some embodiments, the protrusion comprises primary particles and / or secondary particles, and the average diameter of the protrusion is 1μm-20μm (e.g., 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, or within any two of the above values). Controlling the average diameter of the protrusion within the above range can avoid the problem of insufficient protection against punctures of the separator by detached particles due to an excessively small diameter, while also preventing the problem of excessively high adhesive layer coverage and increased lithium-ion transport resistance due to an excessively large diameter, thereby improving the safety and cycle stability of the battery.
[0083] In this invention, the average diameter of the protrusion can be obtained by the following method: On the scanned image, draw the smallest square or rectangle that completely surrounds one protrusion; that is, draw a square or rectangle whose edge meets all four sides of the square or rectangle. The length of one side of the square or the long side of the rectangle is the diameter of the protrusion. Take any 100μm × 100μm area on the polymer coating surface, and average the diameters of any 50 protrusions to obtain the average diameter. Repeat this operation five times, and take the average value to obtain the average diameter of the protrusion. It should be noted that if 50 protrusions can be observed in the captured image, the average diameter of any 50 protrusions in that image is taken. If no 50 protrusions are observed in the image, take multiple images, and average the total number of diameters of the 50 protrusions to obtain the average diameter. The scanned images can be obtained by observing the surface of the polymer layer using a scanning electron microscope (S-3400N, manufactured by Hitachi, Ltd.).
[0084] In some embodiments, the first polymer includes fluorinated polymers and / or non-fluorinated polymers.
[0085] In some embodiments, the fluoropolymer includes one or more of vinylidene fluoride, tetrafluoroethylene, and hexafluoroethylene polymerized to form a fluoropolymer.
[0086] In some embodiments, the non-fluorinated polymers include non-fluorinated polymers formed by polymerizing one or more of styrene, ethylene, propylene, acrylonitrile, methyl methacrylate, butyl acrylate, isooctyl acrylate, octadecyl acrylate, ethyl acrylate, amides, and imides.
[0087] In some embodiments, the polymer layer is made of at least one of the following materials: polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polysulfonamide (PSA), and aramid (poly(m-phenylene isophthalamide)). The polymer layer formed by these materials has good interfacial adhesion, ensuring that the protrusion maintains structural integrity during long-term cycling.
[0088] In some embodiments, the carrier layer includes a substrate layer and a heat-resistant layer located on at least one side surface of the substrate layer. The heat-resistant layer includes heat-resistant particles, and the heat-resistant particles are composed of at least one of alumina, magnesium oxide, boehmite, zirconium oxide, and silicon dioxide.
[0089] In some embodiments, the battery further includes an electrolyte, which may be a conventional electrolyte in the art. For example, the electrolyte may include lithium salts, organic solvents, and additives.
[0090] In some embodiments, the battery is a lithium-ion secondary battery.
[0091] This invention also provides a method for synthesizing silicon-carbon materials: spherical porous carbon is prepared through steps such as template method, hydrothermal method, and activation using a carbon source (e.g., phenolic resin microspheres). Then, silane gas (e.g., SiH4) is introduced at a suitable temperature (e.g., 500-600℃) via chemical vapor deposition (CVD) to thermally deposit silicon in the pores and surface of the porous carbon. Subsequently, carbon source gas can be introduced again for carbon coating modification. Finally, a silicon-carbon composite material with the morphology (first inner angle) and composition (silicon content S) required by this invention is obtained.
[0092] The present invention will be described in detail below through embodiments. The embodiments described herein are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0093] The following examples illustrate the battery of the present invention.
[0094] Example 1 (1) Preparation of negative electrode A negative electrode active material (spherical silicon-carbon particles (sphericity 0.98) and artificial graphite particles, wherein the weight ratio of spherical silicon-carbon particles to artificial graphite particles is 40:60), carbon nanotubes, sodium carboxymethyl cellulose, and PAA are mixed in a mass ratio of 96.9:0.5:0.8:1.8, and deionized water is added to prepare a negative electrode slurry. The above negative electrode slurry is coated on both sides of a copper foil, and then dried, rolled, and die-cut to obtain a negative electrode sheet. The weight percentage of silicon in the negative electrode active layer is 20.3%.
[0095] (2) Preparation of positive electrode sheet Lithium cobalt oxide (the first particle has a Dv50 of 10.3 μm, the second particle has a Dv50 of 3.7 μm, and the weight ratio of the first particle to the second particle is 7.5:2.5), a conductive agent (a mixture of conductive carbon black and carbon nanotubes), and PVDF were placed in NMP at a mass ratio of 97.6:1.35:1.05 and stirred evenly to prepare a positive electrode slurry. The positive electrode slurry was uniformly coated on both sides of an aluminum foil, and then dried, rolled, and die-cut to obtain a positive electrode sheet with a single-sided positive electrode active layer thickness H2 of 56 μm. Multiple groove regions are formed on the first surface using a laser wire bonding device. The groove regions are located in the arc region. The positive electrode active layer has two opposite ends along the first direction, and the grooves connect the two ends. The average depth H1 of the groove is 19 μm, H1 / H2=19 / 56=0.34, the width of the groove is 100 μm, and the spacing between two adjacent grooves is 2.0 mm. The following conditions are met: in the extension direction of the groove, the difference between the distance from the bottom of the groove to the first surface at any two positions in a single groove is 0-3 μm; the difference between the widths of any two different groove regions along the winding direction of the positive electrode sheet is less than or equal to 2 mm; and the major axis of the first positive electrode active particle in the first region of a single groove is 15.8 μm.
[0096] (3) Preparation of electrolyte Under an argon atmosphere and in an environment with a water content of less than 10 ppm, lithium hexafluorophosphate was mixed with an organic solvent (ethylene carbonate (EC): propylene carbonate (PC): propyl propionate (PP): diethyl carbonate (DEC) = 1:1:1:1, mass percentage) to prepare an electrolyte with a lithium salt concentration of 1.05 mol / L. Fluoroethylene carbonate was then added at 20% of the total mass of the electrolyte. After stirring until homogeneous, the electrolyte was obtained after passing tests for moisture and free acid.
[0097] (4) Preparation of the diaphragm A substrate layer with a puncture strength of 400.0 gf is used. A ceramic layer is coated on one side of the substrate layer, and a polymer layer is coated on the side of the ceramic layer away from the substrate layer and on the other side of the substrate layer. The substrate layer is composed of PE, the ceramic layer includes alumina, and the polymer layer is PVDF.
[0098] (5) Preparation of lithium-ion batteries The positive electrode sheet obtained in step (2), the separator obtained in step (4), and the negative electrode sheet obtained in step (1) are wound together to form a bare battery cell. Then, the bare battery cell is placed in an aluminum-plastic film, and the electrolyte obtained in step (3) is injected into the dried bare battery cell. After vacuum sealing, room temperature standing, and high temperature formation, a lithium-ion battery is obtained. The side of the separator with the ceramic layer corresponds to the positive electrode sheet, and the other side of the separator corresponds to the negative electrode sheet.
[0099] Example 2 group This set of examples illustrates the effects of altering the puncture strength of the diaphragm's substrate layer by changing at least one of the molecular weight of the substrate layer or the manufacturing process.
[0100] Example 2a The procedure was carried out in accordance with Example 1, except that the puncture strength of the substrate layer of the diaphragm was adjusted to 201.5 gf.
[0101] Example 2b The procedure was carried out in accordance with Example 1, except that the puncture strength of the substrate layer of the diaphragm was adjusted to 599.6 gf.
[0102] Example 3 Group This set of examples illustrates the effects that occur when H1 / H2 changes.
[0103] This embodiment group is based on Embodiment 1, except that H1 / H2 is changed, as detailed in Table 1-1.
[0104] Table 1-1 Example 4 group Example 4a The same procedure was followed as in Example 1, except that the width of the groove was 20 μm and the distance between two adjacent grooves was 5 mm.
[0105] Example 4b The same procedure was followed as in Example 1, except that the width of the groove was 200 μm and the distance between two adjacent grooves was 0.1 mm.
[0106] Example 5 group Example 5a The process is carried out with reference to Example 1, except that the laser scribing process is changed so that the difference between the maximum and minimum groove depths in a single groove is 8.3 μm in the extension direction of the groove.
[0107] Example 5b The process is carried out with reference to Example 1, except that the laser scribing process is changed so that the difference between the maximum and minimum groove depths in a single groove is 5.2 μm in the extension direction of the groove.
[0108] Example 5c The process is carried out with reference to Example 1, except that the laser scribing process is changed so that the difference between the maximum and minimum groove depths in a single groove is 15.0 μm in the extension direction of the groove.
[0109] Example 6 The same procedure was followed as in Example 1, except that the spherical silicon-carbon particles were replaced with silicon-carbon particles with a first interior angle in their cross-sectional profile, and the angle of the first interior angle was 280°.
[0110] Example 7 Referring to Example 1, the negative electrode active layer includes a first active layer and a second active layer. The first active layer is located between the negative electrode current collector and the second active layer. The weight percentage of the second silicon carbon particles in the first active layer is 7.5% (artificial graphite particles, carbon nanotubes, sodium carboxymethyl cellulose, and PAA are adjusted proportionally according to Example 1). The weight percentage of the first silicon carbon particles in the second active layer is 50.2% (artificial graphite particles, carbon nanotubes, sodium carboxymethyl cellulose, and PAA are adjusted proportionally according to Example 1). The cross-sectional profiles of the first and second silicon carbon particles both have a first interior angle, and the angle of the first interior angle is greater than 180°.
[0111] Example 8 group This set of examples illustrates the effects of providing protrusions in the polymer layer of the diaphragm.
[0112] This embodiment group is based on Embodiment 1, except that a plurality of protrusions formed by a first polymer are provided in the polymer layer of the diaphragm, as detailed in Tables 1-2.
[0113] Table 1-2 Example 9 group This set of embodiments is used to illustrate the effects of changing the major diameter of the first positive electrode active particle in the first region at the edge of the groove by changing one or more of the median particle size of the first particle, the median particle size of the second particle, and the ratio of the weight of the first particle to the weight of the second particle, while adjusting the laser scribing process conditions.
[0114] Example 9a The same procedure was followed as in Example 1, except that the major diameter of the first positive electrode active particle in the first region of the groove edge was 10.2 μm.
[0115] Example 9b The same procedure was followed as in Example 1, except that the major diameter of the first positive electrode active particle in the first region of the groove edge was 25.3 μm.
[0116] Example 9c The same procedure was followed as in Example 1, except that the major diameter of the first positive electrode active particle in the first region of the groove edge was 29.6 μm.
[0117] Comparative Example 1 The procedure was carried out in accordance with Example 1, except that one or more of the following were changed: the median particle size of the first particle, the median particle size of the second particle, and the ratio of the weight of the first particle to the weight of the second particle. At the same time, the laser scribing process conditions were adjusted so that the major diameter of the first positive electrode active particle in the first region at the edge of the groove was 32.4 μm.
[0118] Comparative Example 2 The procedure was carried out in accordance with Example 1, except that the puncture strength of the substrate layer of the diaphragm was adjusted to 180.0 gf by changing the molecular weight of the substrate layer and at least one of the preparation processes.
[0119] Comparative Example 3 The same procedure was followed as in Example 1, except that the weight percentage of silicon in the negative electrode active layer was adjusted to 51%.
[0120] Test case The batteries prepared in the examples and comparative examples were subjected to the following tests: 1. Lithium plating test The lithium-ion batteries were subjected to cyclic testing in a test cabinet under the following conditions: 5 minutes of resting at 25℃±2℃, charging to 4.35V at 2.5C, charging to 4.55V at 1C, and stopping at 0.05C. The battery capacity was then measured. Subsequently, the batteries were discharged to 3.0V at 0.7C, and this process was repeated 500 times. The disassembled images of the battery cells after 500 cycles at full charge were observed to examine the lithium plating at the negative electrode interface, especially at the top and bottom edges. The degree of lithium plating was categorized as no lithium plating (the negative electrode is golden yellow), slight lithium plating (local gray deposits on the edges of the negative electrode surface), and severe lithium plating (large areas of white lithium metal or grayish-black deposits on the edges of the negative electrode). The order was: severe lithium plating > slight lithium plating > no lithium plating.
[0121] 2. Self-discharge level K-value test The batteries prepared in each embodiment and comparative example were charged to 4.55V at 0.2C constant current and constant voltage at 25℃±3℃, with a cutoff current of 0.05C. After standing for 30 minutes, the open-circuit voltage V1 was measured, and then the open-circuit voltage V2 was measured again after standing at 25℃ for 48 hours. The voltage drop ΔV = V1 - V2 was calculated. The K value was calculated using the formula: K = ΔV / 48, in mV / h. Twenty cells were tested for each embodiment or comparative example, and the average value was taken as the K value for that sample.
[0122] 3. Cyclic life performance test The lithium-ion batteries were subjected to cycle testing in a test cabinet under the following conditions: 5 minutes of resting at 25℃±2℃, charging to 4.35V at 2.5C, charging to 4.55V at 1C, and then stopping at 0.05C to measure the battery capacity. Subsequently, the batteries were discharged to 3.0V at 0.7C, and this process was repeated 800 times. The capacity of the first discharge was designated Q1, and the capacity of the 800th discharge was designated Q2. Cycle life was measured by the capacity retention rate C; a higher C was better, and a lower C was worse. C = (Q2 / Q1) × 100% 4. Ratio performance At 25℃±2℃, the battery is discharged to 3V at a constant current of 0.2C, and the initial discharge capacity is recorded as Q0. After standing for 10 minutes, it is fully charged at 0.7C (100% SOC), with a cutoff current of 0.025C. After standing for 10 minutes, it is discharged to 3V at a 2C rate and then stood for 10 minutes. The discharge capacity at this time is recorded as Q1. The rate discharge capacity retention rate is: (Q1 / Q0)×100%.
[0123] The results are recorded in Table 2.
[0124] Table 2 As can be seen from Table 2, by comparing the proportions and examples, it can be seen that by controlling the long diameter of the first positive electrode active particle in the first region, the puncture strength of the substrate layer of the separator, and the weight ratio of silicon in the negative electrode active layer, the battery's self-discharge level is reduced, and the battery's cycle performance and rate performance are improved while the severe lithium plating of the battery is improved.
[0125] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A battery, characterized in that, The device includes an electrode assembly comprising a positive electrode sheet, a separator, and a negative electrode sheet stacked together. The positive electrode sheet includes a positive current collector and a positive active layer located on at least one side surface of the positive current collector. The positive active layer includes positive active particles. The surface of the positive active layer away from the positive current collector is a first surface. The first surface includes at least one groove region. The groove region is provided with a plurality of grooves at intervals. The average depth of the grooves is H1. In at least one of the grooves, the edge of the groove includes a first region at a distance of 0-0.5H1 from the first surface. The first region includes a first positive active particle. The major axis of the first positive active particle is less than or equal to 30 μm. The puncture strength of the substrate layer of the diaphragm is greater than or equal to 200 gf, the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer located on at least one side surface of the negative electrode current collector, and the weight ratio of silicon element is less than or equal to 50% based on the total weight of the negative electrode active layer.
2. The battery according to claim 1, wherein, The battery satisfies the following relationship: 0.2≤H1 / H2≤0.5, where H2 is the thickness of the positive electrode active layer on one side; And / or, the width of the groove is 20μm-200μm; And / or, the spacing between any two adjacent grooves is 0.1mm-5mm; And / or, the average depth H1 of the groove is greater than or equal to 5 μm; And / or, the puncture strength of the substrate layer of the diaphragm is 200gf-600gf.
3. The battery according to claim 1, wherein, The electrode assembly includes a flat region and arc regions located at both ends of the flat region; the positive electrode includes a plurality of first bending segments located in the arc regions and arranged sequentially from the inside to the outside, and at least one of the first bending segments is provided with the groove region; And / or, the positive electrode active layer has two opposing ends along a first direction, and the groove connects the two ends; And / or, the positive electrode active layer has two opposite ends along the first direction, and the groove is at a distance from both ends.
4. The battery according to claim 1, wherein, Along the winding direction of the positive electrode sheet, the difference between the widths of any two different groove regions is less than or equal to 2 mm. Preferably, the width of the groove region is 6 mm to 12 mm. Alternatively, the electrode assembly includes a flat region and arcuate regions located at both ends of the flat region; the positive electrode includes a plurality of first bending segments arranged sequentially from the inside to the outside in the arcuate regions, each of the plurality of first bending segments being provided with a groove region; along the radial direction of the electrode assembly from the inside to the outside, the first N of the plurality of first bending segments constitute a first region, the N+1 to N+M of the plurality of first bending segments constitute a second region, and the N+M+1 to N+M+Q of the plurality of first bending segments constitute a third region, the width of the groove region in the first region is W1, the width of the groove region in the second region is W2, and the width of the groove region in the third region is W3, wherein W1 < W2 < W3; 4 ≤ N ≤ 8, 3 ≤ M ≤ 10, 5 ≤ Q ≤ 35; preferably, W1 is 2mm-5mm, W2 is 4mm-8mm, and W3 is 6mm-12mm.
5. The battery according to any one of claims 1-4, wherein, In the extending direction of the groove, the difference in distance from the bottom of the groove to the first surface at any two locations within a single groove is 0-3 μm.
6. The battery according to any one of claims 1-4, wherein, In the extending direction of the groove, the difference between the maximum groove depth and the minimum groove depth in a single groove is 5μm-15μm.
7. The battery according to claim 1, wherein, The positive electrode active particles include a first particle and a second particle. The median particle size Dv50 of the first particle is 12μm-20μm, and the median particle size Dv50 of the second particle is 2μm-5μm. The weight ratio of the first particle to the weight of the second particle is (6-9):(1-4). And / or, the positive electrode active particles include at least one of lithium cobalt oxide and lithium iron phosphate; And / or, the negative electrode active layer includes silicon carbon particles, the cross-sectional profile of which has a first interior angle, the angle of which is denoted as B°, where B > 180°.
8. The battery according to claim 1, wherein, The diaphragm includes a carrier layer and a polymer layer located on at least one side of the carrier layer. The polymer layer includes a plurality of protrusions formed of a first polymer on the surface away from the carrier layer, and the average height of the protrusions is 0.5 μm-15 μm. Preferably, the protrusion comprises primary particles and / or secondary particles, and the average diameter of the protrusion is 1μm-20μm; Preferably, the carrier layer includes a substrate layer and a heat-resistant layer located on at least one side surface of the substrate layer, the heat-resistant layer includes heat-resistant particles, and the composition of the heat-resistant particles includes at least one of alumina, magnesium oxide, boehmite, zirconium oxide, and silicon dioxide. Preferably, the first polymer includes fluorinated polymers and / or non-fluorinated polymers.
9. The battery according to claim 1, wherein, The negative electrode active layer includes a first active layer and a second active layer. The first active layer is located between the negative electrode current collector and the second active layer. The first active layer includes graphite, and the second active layer includes first silicon carbon particles.
10. The battery according to claim 9, wherein, The first active layer further includes second silicon carbon particles, wherein the weight percentage of silicon in the second active layer is greater than that of silicon in the first active layer. Preferably, the weight percentage of the second silicon carbide particles in the first active layer is 0-15%, and the weight percentage of the first silicon carbide particles in the second active layer is 10%-90%.